The Effectiveness of Entrepreneurship Management on the Mosque Prosperity Agency in Langsa in the terms of Sharia - Zulkarnen Mora; Dias Setianingsih; Bustami Bustami (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The Mosque Prosperity Body (BKM) has a central role in managing the economy of people who practice worship as a goal of life in kafah. In Islam itself, welfare is a major milestone in the implementation of Muslim worship. The purpose of this study is to measure the extent to which the effectiveness of entrepreneurship management carried out by BKM in Langsa City in terms of sharia. This research is an exploratory research with a qualitative approach. The sample was selected based on the division of regions, namely 1 Langsa Municipality (BKM Darul Falah) and 5 sub-districts in the Langsa City area which consists of 5 districts, namely East Langsa (BKM Nurul Quran), Langsa Lama (BKM Nurul Iman), Langsa Kota (BKM Taqwa) ), Langsa Baro (BKM Baitul Mukmin), and Langsa Barat (BKM Baitul Aminin). The sample was selected based on the determination of aspects of the application of Idarah (management), Imarah (prosperity) and Ri'ayah (facilities and care). The stages of the research method began with observation, identification, literature review, data collection, designing research instruments, Focus Group Discussion (FGD), data analysis and formulation of research results. The output of this research is targeted to be an article published in an accredited journal 3. In addition, the Technology Readiness Level where the results of this study are expected to become a role model for the application of measuring the effectiveness of entrepreneurial management based on sharia reviews in every mosque prosperity body in Langsa City and Aceh region. and Indonesia in general. Thus the role and function of the mosque prosperity body is increasingly contributive and measured in carrying out its work as a Muslim socio-economic institution with the aim of providing welfare values so that it is more aspirational, of course, even though the results of the research obtained have not met expectations / the implementation of entrepreneurial management at BKM in Langsa City has not been effective. In terms of its imarah function, however, other functions such as idarah and ri'ayah have met the standard criteria.